Egg White Hydrolysate Retains the Nutritional Value of Proteins and Is Quickly Absorbed in Rats - Ryosuke Matsuoka; Hitoshi Kurihara; Noriaki Nishijima; Yoshifumi Oda; Akihiro Handa (The Scientific World Journal)
Egg white protein has a high net protein utilisation, with a score of 100 in the amino acid rating system. Although the enzymatic breakdown of egg white yields hydrolysates that are rapidly absorbed and various physiological activities can be expected from them, flavouring egg white to meet taste requirements as a food has been a difficult challenge. Herein, we developed a high-molecular-weight egg white hydrolysate and compared the absorption rate and nutritional value of the hydrolysate with those of egg white proteins obtained from raw materials, whey proteins, and hydrolysates, also known as high-quality proteins. The absorption rate of egg white hydrolysates was faster than that of egg white and whey proteins in portal vein cannulated rats, and their bioavailability values were higher than those of whey proteins and hydrolysates. According to the protein digestibility-corrected amino acid score and digestible indispensable amino acid score, the scores for egg white hydrolysates were equivalent to those of egg white and whey proteins but higher than those of whey hydrolysates. Our results show that egg white hydrolysates maintain the nutritional value of egg whites and are rapidly absorbed by the body.